Heutagogy for teaching academic writing in Islamic higher education contexts - Muhammad Iksan; Muhammad Basri; Sahril Sahril; Marlia Marlia (Siliwangi University, 2025)
The growing attention paid to learner autonomy in higher education has led to interest in alternative pedagogical frameworks like heutagogy, which advocates for self-determined learning and the development of reflective capability. Nonetheless, actual studies investigating the implementation of heutagogy in academic writing training are limited, especially within the Islamic higher education context. This study examines the comprehension and application of heutagogical principles in academic writing training at a state Islamic higher education institution in eastern Indonesia. A qualitative case study design was utilized, with data gathered through semi-structured interviews with four lecturers and twenty-four undergraduate students, classroom observations, and document analysis over six months. Thematic analysis identified five interrelated themes: diverse interpretations of heutagogy, conflicts between institutional traditions and pedagogical innovation, inconsistent student readiness for self-determined learning, the impact of instructor agency and professional experience, and the contribution of digital technologies to facilitating autonomous writing practices. The findings indicate that although a heutagogical approach promotes reflective learning and learner autonomy, its application is influenced by institutional norms, students’ previous educational experiences, and lecturers’ pedagogical beliefs. The research illustrates the impact of culturally rooted principles and institutional customs on the implementation of learner-centered pedagogies in Islamic higher education, emphasizing the necessity for pedagogical scaffolding and professional development to foster learner autonomy in academic writing instruction. Keywords: Academic Writing, Heutagogy, Learner Autonomy, Islamic Higher Education, Self-Determined Learning